2020
DOI: 10.3389/fimmu.2020.00418
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Effects of Romidepsin on T-Cell Activation, Apoptosis and Function in the BCN02 HIV-1 Kick&Kill Clinical Trial

Abstract: Romidepsin (RMD) is a well-characterized histone deacetylase inhibitor approved for the treatment of cutaneous T-cell lymphoma. in vitro and in vivo studies have demonstrated that it is able to induce HIV-1 gene expression in latently infected CD4 + T cells from HIV-1 + individuals on suppressive antiretroviral therapy. However, in vitro experiments suggested that RMD could also impair T-cell functionality, particularly of activated T cells. Thus, the usefulness of RMD in HIV-1 kick&kill strategies, that aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…Romidepsin is an oral histone deacetylase inhibitor; its effects on the immune system are not fully understood. Both immune cell-suppressive and -enhancing effects have been reported for romidepsin [13, 14]. In this patient, romidepsin had no impact on the reversal of the CD4/CD8 ratio, although the percentages of both CD4-positive and CD8-positive T lymphocytes decreased after 6 cycles of treatment (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Romidepsin is an oral histone deacetylase inhibitor; its effects on the immune system are not fully understood. Both immune cell-suppressive and -enhancing effects have been reported for romidepsin [13, 14]. In this patient, romidepsin had no impact on the reversal of the CD4/CD8 ratio, although the percentages of both CD4-positive and CD8-positive T lymphocytes decreased after 6 cycles of treatment (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The anti-vaccine responses were detected by measuring effector cell cytokines in the ICS assay. Briefly, to exclude dead cells, monocytes and B cells, cells were stained with the Live/Dead fixable Violet Dead cell stain kit (Invitrogen), CD14-Pacific Blue, and CD19-V450 and gated in a dump channel as described (20). Additional surface markers were used to study the T-cell lineages (CD3, CD4, and CD8), T-cell activation (CD38 and HLADR), and maturation phenotypes (CD45RA and CCR7).…”
Section: Intracellular Cytokine Staining (Ics) Assaymentioning
confidence: 99%
“…Some LRAs have also been demonstrated to promote cell death, as seen with benzolactam derivatives that are PKC agonists and induce apoptosis in latent HIV-1-infected cells 65, 66 . A recent report also demonstrated that romidepsin treatment in a clinical trial resulted in an increase in the frequency of apoptotic T cells 67 . Therefore, the link between apoptosis and latency reversal is highly promising to further exploit as a strategy to reactivate the viral reservoir and induce its selective elimination.…”
Section: Discussionmentioning
confidence: 93%